The Effectiveness of Preventation and Relationship Enrichment Program (PREP) on Marital Conflicts and Sexual Satisfaction in Couples - Radpour, Behnoush; Behboodi, Masoumeh; Dokanehi Fard, Farideh (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The objective of this study was to evaluate the effectiveness of the Preventation and Relationship Enrichment Program (PREP) on reducing marital conflicts and enhancing sexual satisfaction among couples in East Tehran. Methods and Materials: This randomized controlled trial involved 40 couples (80 participants) who were randomly assigned to either the intervention group (receiving PREP) or the control group (receiving no intervention). The intervention consisted of ten 75-minute sessions over ten weeks. Data were collected using the Marital Conflict Resolution Scale (MCRS) and the Index of Sexual Satisfaction (ISS) at baseline, post-intervention, and one-month follow-up. Descriptive statistics, repeated measures ANOVA, and Bonferroni post-hoc tests were employed to analyze the data using SPSS version 27. Findings: The intervention group showed significant improvements in marital conflict resolution and sexual satisfaction compared to the control group. The repeated measures ANOVA revealed significant main effects for time and group, and significant time x group interactions for both marital conflicts (F(2, 76) = 11.21, p < .001) and sexual satisfaction (F(2, 76) = 12.63, p < .001). Bonferroni post-hoc tests indicated substantial reductions in marital conflicts from baseline to post-intervention (Mean Difference = -12.13, p < .001) and baseline to follow-up (Mean Difference = -13.66, p < .001), as well as significant increases in sexual satisfaction over the same periods (Mean Difference = 13.67, p < .001 and 15.78, p < .001, respectively). Conclusion: The results highlight the potential of relationship education programs to improve marital quality and suggest their broader applicability across different cultural settings. These findings support the integration of such programs into family counseling services to promote healthier, more satisfying relationships.